Fully developed magnetohydrodynamics natural convection flow in a vertical micro-porous-channel with Hall effects. Issue 2 (June 2019) - Jha, Basant Kumar; Malgwi, Peter Bukar; Aina, Babatunde
An exact solution is presented for the steady hydromagnetic fully developed natural convection flow in a vertical microporous channel due to asymmetric heating. The governing momentum and energy equations are presented in dimensionless form and solved analytically using the method of undetermined coefficient. The effects of Hall current and suction/injection parameters on the primary and secondary velocity, volume flow rates, and skin frictions are discussed with the help of line graphs and tables. It is observed that injection accelerates the flow, whereas suction retards the flow in both the primary and secondary flow directions.